Digital platforms and sustainable business models: a study about food waste recovery - Bruno, Lucrezia (2019)
The United Nation Food and Agriculture Organization estimates that one third of all the food produced for human consumption is wasted each year (FAO, 2017). In that respect, increasing attention has been paid to the inefficiency of the food system due to the significant economic, social and environmental costs associated with it. Until now, and with only few exceptions, impediments on the demand and supply side have hindered the pursuit of sustainable solutions. As Business Platforms gain market share from traditional businesses, the research investigates “When” and “How” they can contribute to delivering sustainability within the food industry by facilitating the exchange of discarded food at the retail, distribution and consumption stages of the food value chain. Specifically, this study seeks to investigate: (1) the opportunities and barriers to the use of Business Platforms for Food Waste Recovery; (2) the inherent challenges; (3) the main strategies followed and (4) the benefits generated. The study starts by analyzing extant literature on business models, sustainable innovation, food sustainability and business platforms. Ninety-four food waste recovery platforms are identified by fieldwork, thirteen of which are B2C organizations. Then, five of these B2C are analyzed by conducting twenty-two semi-structured interviews with the subjects who currently manage and lead these organizations.The results of the interviews are elaborated in parallel with secondary data using a coding process aimed at developing a framework for analyzing a specific type of business platform for sustainability, i.e. the Food Waste Recovery Business Platform. In conclusion, the findings and the framework are discussed in relation to existing literature, highlighting existing gaps compared to earlier studies and possible developments for further research.